PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII5 SMP NEGERI 35 PEKANBARU - Adli, Ariful; Solfitri, Titi; Anggraini, Rini Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThis research aimed to improve learning process and mathematics learning outcomes in SMP Negeri 35 Pekanbaru by implementing Structural Approach to Cooperative Learning Model Numbered Heads Together (NHT). Subjects of the research were students grade VII5 who have the academic ability of the heterogeneous. This research is a classroom action research with two cycles. Each cycle has four stages, the stages are planning, action, observation and reflection. The results show the activity of teachers and students have done well after doing the action. There was enchanment in the number of students who achieved KKM (minimum criteria of achievement) in formative test at the end of each cycle is compared to the number of students who achieve KKM on base score. Starting from 25% increased to 35% and increased to 77,5%. There was also an increasing in the number of students who scored 20 and 30 is compared to the development of the number of students who received grades 5 and 10. Results of this research indicate that the application of Structural Approach to Cooperative Learning Model Numbered Heads Together (NHT) can improve learning process and improve the mathematics learning outcomes of students grade VII5 SMP Negeri 35 Pekanbaru in the first semester academic year 2013/2014.Key words: Mathematics learning outcome, Cooperative learning, Numbered Heads , Class action research.